Testing the Representativeness of a Multimode Survey in South Korea: Results From KAMOS - Sung Kyum Cho; Sarah Prusoff LoCascio; Kay-O Lee; Deok-Hyun Jang; Jong Min Lee (Asian Journal for Public Opinion Research, 2017)
The Korean Academic Multimode Open Survey (KAMOS) is a national survey first conducted in 2016. Stratified cluster random sampling was used in an initial face-to-face survey during which panel members were recruited. The second survey allowed invited panel members to answer online or by phone. KAMOS includes both longitudinal items and omnibus items, i.e., researchers can propose questions to include on KAMOS. This paper seeks to establish that KAMOS is representative of the South Korean adult population. The demographic variables from the first survey were comparable to demographic variables from two well-respected surveys in South Korea: the KOSTAT Social Survey and the Gallup Korea Omnibus Survey. To ensure that there was no substantial difference between those who answered the first survey and those who answered the second survey, we compared the results of 22 items from the first survey. The 2,000 panel members who were invited to participate in the second survey had similar responses to the 1,008 of those who responded to the second survey. Based on our findings, KAMOS can be considered a representative sample.